Tradisi Mudas dalam Budaya Dayak di Meliau, Kalimantan Barat Dari Sudut Pandang Orang Luar - Tampani, Kondradus; Jegaut, Siprianus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
This article focuses on “Mudas Tradition of the Dayak Culture in Meliau District, Sanggau Regency, West Kalimantan.” The tradition of clearing land in Dayak culture in Meliau District is commonly called “Mudas”. Mudas culture is one of the customs carried out by the Dayak society before cultivating a new land. This Mudas ceremony is a form of their respect for nature. The methodology used in this research is a narrative method through experiences through the Mudas culture in Meliau, West Kalimantan and in principle is supported by library sources through books and journals. The first and the main purpose of this is to know the Mudas culture from the perspective of the author as an outsider and how other people interact in that culture. The author concludes that the Mudas Tradition in Dayak culture is not much different from its original culture, which prioritizes respect to Nature in every day life. Nature is everything for human life, especially for the Dayak people in Meliau, West Kalimantan.